Generation Z "life skills" acquired and enhanced through internships before and during COVID-19 pandemic - Eriona Shtembari; Riza Feridun Elgün (Administrative Sciences, 2023)
The paper explores "life skills" acquired and enhanced during an internship in preparation for the work of the future, identifies challenges faced and gaps between academic preparation and internship requirements, and explores the impact of the COVID 19 pandemic on the internship experiences of Generation Z students. This qualitative study involves cohorts from 2016-2021, including 50 students before the pandemic, and 47 students during the pandemic, majoring in the field of Economy and Business. Data are gathered through 97 semi-structured interviews and written reports from the students. Interestingly, the findings showed that job placement is not the main reason why students pursue an internship; acquiring skills and experience was identified as the major motivating factor. "Communication" was the top enhanced skill from internships in both periods before and during the pandemic, while "relationship building" and "ethical issues" ranked as the second and third most important skills before the pandemic, to be replaced by "critical-thinking and problem-solving" and "analytical and technical" skills during the pandemic. Lack of accountability and COVID-19 stress were reported as the main challenges experienced during internships, while lacking hands-on experience and social skills were identified as gaps. The foremost pieces of advice for future interns revealed in this study are to get involved seriously and show respect and integrity.
Keywords: 350; challenges; COVID-19; Internship; skills